Effects of medical causes, role concepts and treatment stages on quality of life in involuntary childless men. (14th January 2016) - Schick, M.; Rösner, S.; Toth, B.; Strowitzki, T.; Jank, A.; Kentenich, H.; Thöne, C.; Wischmann, T.
Summary: Goal of this study was to investigate differences in quality of life in men contingent upon various fertility treatment stages, infertility causes and adoption of roles. A quantitative study with n  =   115 men in three German fertility centres was devised. Participants completed a standardised, fertility‐specific questionnaire devised for men (TLMK), sociodemographic and role items. Men having experienced severe medical conditions, for example cancer, reported significant higher quality of life compared to men with other infertility reasons [ F (1, 56) = 12.77, P  =   0.001]. Furthermore, allocating participants into distinctive groups by means of kind and duration of treatment revealed significant group differences [ F (2, 111) = 4.94, P  =   0.009], with quality of life decreasing with the use of more invasive fertility methods. A higher satisfaction with life was also stated by men adopting many tasks in the treatment process. The high quality of life displayed by men having experienced severe medical conditions contains valuable and far‐reaching information about possible resilience factors that need to be researched more in detail. The finding of decreasing quality of life in men with the use of more invasive methods in treatment applies for increased psychosocial services in fertility clinics.